Throughfall and output fluxes of Mg in European forest ecosystems: a regional assessment - Armbruster M.; MacDonald J.; Dise N.B.; Matzner E.
The biogeochemistry of Mg is of special importance in terrestrial ecology since Mg deficiency is a widespread phenomenon in European forests. Here, we investigate regional patterns of annual Mg fluxes with throughfall in relation to Mg outputs with seepage and runoff using published data from 71 forest ecosystems. Throughfall fluxes of Mg in this dataset are between 0.24 and 22.4kgha-1yr-1 and are related to two major factors: the distance to the sea and the amount of dust in deposition. The gradient of Mg input from the sea may extend to 200km inland. Output fluxes of Mg are on an average higher than throughfall input fluxes, with an average net loss of Mg from most ecosystems of 0.5-1.5kgha-1yr-1 despite widespread Mg deficiency in European forest ecosystems. The amount of Mg leached in runoff or seepage water is largely dependent on the amount of Mg in throughfall. The influence of soil conditions and bedrock type on Mg output are surprisingly minor in this database indicating that the Mg cycle in many European forest ecosystems is to a great extent influenced by atmospheric inputs of Mg.
Keywords: BUDGET; EUROPE; FLUXES; FOREST; MAGNESIUM; RUNOFF; SEEPAGE; THROUGHFALL; WEATHERING